Salvation and Eternal Life in an Alternative Religious Movement – The Raëlian Book of the Cloned - Danijel Sinani (Etnoantropološki Problemi, 2016)
The paper examines the conceptualization of salvation and eternal life within the Raëlian movement. After a brief overview of this alternative religious movement, we will give an analysis of certain aspects of the movement’s religious teachings relevant for our paper. Based on a specific biblical exegesis and latter developments of the basic teachings, the founder of the movement and his disciples bring a wholly new interpretation of these, perhaps most important religious themes. By positioning intelligence and science into the focus of their eschatology, Raelians introduce the idea of cloning as a path to eternal life. However, even with the attempts made by the founder to represent the Raelian belief system as a total break from the “primitive” understanding and practices of religion, the holy texts of this movement do contain old religious ideas as well as other familiar mechanisms of engaging the religious commitment of its members.